Multiomics profiling of DNA methylation, microRNA, and mRNA in skeletal muscle from monozygotic twin pairs discordant for type 2 diabetes identifies dysregulated genes controlling metabolism - Charlotte Ling; Magdalena Vavakova; Bilal Ahmad Mir; Johanna Säll; Alexander Perfilyev; Melina Martin; Per-Anders Jansson; Cajsa Davegårdh; Olof Asplund; Ola Hansson; Allan Vaag; Emma Nilsson (BMC Medicine)
Abstract Background A large proportion of skeletal muscle insulin resistance in type 2 diabetes (T2D) is caused by environmental factors. Methods By applying multiomics mRNA, microRNA (miRNA), and DNA methylation platforms in biopsies from 20 monozygotic twin pairs discordant for T2D, we aimed to delineate the epigenetic and transcriptional machinery underlying non-genetic muscle insulin resistance in T2D. Results Using gene set enrichment analysis (GSEA), we found decreased mRNA expression of genes involved in extracellular matrix organization, branched-chain amino acid catabolism, metabolism of vitamins and cofactors, lipid metabolism, muscle contraction, signaling by receptor tyrosine kinases pathways, and translocation of glucose transporter 4 (GLUT4) to the plasma membrane in muscle from twins with T2D. Differential expression levels of one or more predicted target relevant miRNA(s) were identified for approximately 35% of the dysregulated GSEA pathways. These include miRNAs with a significant overrepresentation of targets involved in GLUT4 translocation (miR-4643 and miR-548z), signaling by receptor tyrosine kinases pathways (miR-607), and muscle contraction (miR-4658). Acquired DNA methylation changes in skeletal muscle were quantitatively small in twins with T2D compared with the co-twins without T2D. Key methylation and expression results were validated in muscle, myotubes, and/or myoblasts from unrelated subjects with T2D and controls. Finally, mimicking T2D-associated changes by overexpressing miR-548 and miR-607 in cultured myotubes decreased expression of target genes, GLUT4 and FGFR4, respectively, and impaired insulin-stimulated phosphorylation of Akt (Ser473) and TBC1D4. Conclusions Together, we show that T2D is associated with non- and epigenetically determined differential transcriptional regulation of pathways regulating skeletal muscle metabolism and contraction.